Women in the Vortex of Local Power: The Politics of Kinship and Leadership of the Head of Sungai Pinang Village, Rambutan District, Banyuasin Regency - Rodiansa; Amaliatulwalidain; Isabella (Universitas Muhammadiyah Palu, 2025)
This research aims to find out and understand how female village heads are in the vortex of kinship politics in Sungai Pinang Village, Rambutan District, Banyuasin Regency in 2024. This study uses a qualitative methodology with interview, observation, and documentation techniques to collect data. This research uses the theory of familiesties (Jalalzai & Rincker 2018) and the theory of Women and Politics (Joni Lovenduski 2025). The results of this study show that kinship relationships have a significant influence on the process of electing female village heads with family support, social capital, and community solidarity that are still strong in traditional structures in the village. Kinship politics is not only a power strategy but also a means for women to gain legitimacy in leadership in villages that are still patriarchal. This research confirms that kinship politics has a positive and negative impact on village democracy, on the one hand facilitating women's access to be involved in village politics, but can also strengthen the practice of political dynasties that close the space for community participation at large. In conclusion, the head of the female village in Sungai Pinang Village is influenced by the practice of kinship politics (familyties) which has been firmly rooted in the local social and political structure. The suggestion that the researcher can give is an effort to improve the quality of village democracy so that women's representation is not only symbolic but also substantive.